Anti-bacterial Activity of Prenylated Xanthone from The Bark of Garcinia lowa - Darwati Darwati; Elisabeth Krismayanti; Supriyatna Supriyatna; Unang Supratman (Jurnal Kimia Valensi, 2016)
Bioactivity-guided fractionation of a ethyl acetate extract of Garcinia lowa bark has led to the isolation and identification of a known prenylated xanthone, mangosharin, (2,6-dihydroxy-8-methoxy-5-(3-methylbut-2-enyl)-xanthone (1, 15.4 mg) The structure of the compound was identified from analysis of their spectroscopic data and by comparison with previous studies.Compound 1 showed anti-bacterial activity against Sreptococcus mutans with MIC value of 7.25 mg/mL. DOI : http://dx.doi.org/10.15408/jkv.v0i0.4057